Mechanisms For Organizing Tax Control In The Business Environment Based On Risk Analysis (American Economist: Journal of Economics Finance and Global Policy, 2026)
This article develops a new methodological approach to improving tax administration in the entrepreneurial environment of Uzbekistan. Unlike traditional approaches that treat tax administration mainly as a mechanism of control, the article frames it as an institutional infrastructure that should reduce compliance costs, increase trust, protect honest taxpayers and identify high-risk behaviour through data-based tools. The study uses a mixed-method desk research design based on official statistics on small business development, State Tax Committee information on budget receipts and digitalisation measures, the World Bank Enterprise Survey 2024 for Uzbekistan, and policy guidance from the OECD, IMF and World Bank. The empirical results show that small business is a systemic sector of the Uzbek economy: in January-September 2025 it accounted for 51.5 percent of GDP, 75.7 percent of construction, 60.9 percent of fixed investment, 55.0 percent of services, 32.0 percent of exports and 53.7 percent of imports. At the same time, World Bank firm-level data indicate that most firms do not perceive tax administration as a severe obstacle, but about one fifth of surveyed cases still report moderate or higher obstacles. This creates a reform challenge: tax administration should not become softer toward non-compliance, but it must become more selective, predictable and integrated with the business processes of taxpayers. The article proposes the Entrepreneurial Tax Administration Improvement Index (ETAI-5), consisting of simplification, digital integration, risk fairness, service quality and transparency
Keywords: tax administration; entrepreneurship; small business